Fear causes tears - Perineal injuries in home birth settings. A Swedish interview study - Brink Åsa; Lindgren Helena E; Klinberg-Allvin Marie (BMC, 2011)
Abstract Background Perineal injury is a serious complication of vaginal delivery that has a severe impact on the quality of life of healthy women. The prevalence of perineal injuries among women who give birth in hospital has increased over the last decade, while it is lower among women who give birth at home. The aim of this study was to describe the practice of midwives in home birth settings with the focus on the occurrence of perineal injuries. Methods Twenty midwives who had assisted home births for between one and 29 years were interviewed using an interview guide. The midwives also had experience of working in a hospital delivery ward. All the interviews were tape-recorded and transcribed. Content analysis was used. Results The overall theme was "No rushing and tearing about", describing the midwives' focus on the natural process taking its time. The subcategories 1) preparing for the birth; 2) going along with the physiological process; 3) creating a sense of security; 4) the critical moment and 5) midwifery skills illuminate the management of labor as experienced by the midwives when assisting births at home. Conclusions Midwives who assist women who give birth at home take many things into account in order to minimize the risk of complications during birth. Protection of the woman's perineum is an act of awareness that is not limited to the actual moment of the pushing phase but starts earlier, along with the communication between the midwife and the woman.